VOCABULARY LEARNING AND VOCABULARY LEARNING STRATEGIES - Usein, Arafat (International Scientific Journal Vision, 2022)
Vocabulary learning is an important component in language learning and of critical importance to the typical language learner. It is a basic constituent of learning a language. If students lack vocabulary they will be unable to function in any particular communication. Also, the grammar or the structure of a language is also important. But if we wish to express ourselves effectively we need enough vocabulary. The more words we know, the better we understand what we read and listen to. Unfortunately, the importance of vocabulary teaching is being neglected by most of the language teachers. They assume that their students will learn words incidentally. It is thought that vocabulary expansion will happen through the practice of other language skills. Teachers need to be aware of and expand vocabulary teaching techniques. Furthermore, the language teacher needs to have a deep knowledge on Vocabulary Language Strategies, thus find systematic ways of helping learners in building vocabulary. This paper deals with some of the ways vocabulary is taught by pointing out the Vocabulary Learning, Learning Strategies and Vocabulary Learning Strategies.